Health Care Needs Across Different Age Groups in Children with Cerebral Palsy: A Survey (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background: Cerebral palsy (CP) is the most common chronic childhood disability of today. Health care needs arepresent in these children who require health services to manage their functional disability. It can change accordingto the age group and severity of the condition. In the current healthcare system, little is known about prioritiesand needs for the children with cerebral palsy especially in reference to Indian contextual situations and how theseneeds may differ based on the child’s age and motor function.Methods: A cross sectional survey design is used in the study. 83 parents of children with cerebral palsy and theirtreating physiotherapists were selected in the study based on the inclusion and exclusion criteria. Participantswere divided into 3 groups based on the age of the children. Self designed questionnaire was given to the parentsand the physiotherapists to select the health care needs for the children. One time data collection was done overthe period of 3 months.Conclusion: The study also shows that mostly parent’s needs are considered by physiotherapists for their goalsettings. Most of the time parents’ needs and the physiotherapist’s goals are found to be similar.
Keywords: Cerebral Palsy, Health care needs, parents, physiotherapists